Recent advances in constructed wetlands methane reduction: Mechanisms and methods - Yu, Guanlong; Chen, Jundan; Wang, Guoliang; Chen, Huifang; Huang, Jiajun; Li, Yifu; Wang, Wenming; Song, Fengming; Ma, Yuanjun; Wang, Qi; Wang, Miaomiao; Ling, Tao; et al. (Frontiers in Microbiology, 2023)
Constructed wetlands (CWs) are artificial systems that use natural processes to treat wastewater containing organic pollutants. This approach has been widely applied in both developing and developed countries worldwide, providing a cost-effective method for industrial wastewater treatment and the improvement of environmental water quality. However, due to the requirement for large organic carbon inputs, CWs generate varying amounts of CH4 and have the potential to become an important contributor to global climate change. Subsequently, research on the mitigation of CH4 emissions by CWs is key to achieving sustainable, low-carbon dependency wastewater treatment systems. This review evaluates the current research on CH4 emissions from CWs through bibliometric analysis, summarizing the reported mechanisms of CH4 generation, transfer and oxidation in CWs. Furthermore, the important factors driving CH4 generation in CW systems are summarized, including: temperature, water table position, oxidation reduction potential, and the effects of CW characteristics such as wetland type, plant species composition, substrate type, CW-coupled microbial fuel cell, oxygen supply, available carbon source, and salinity. This review provides guidance and novel perspectives for sustainable and effective CW management, as well as for future studies on CH4 reduction in CWs.